(untitled) (Indian Journal of Animal Production and Management, 2017)
A study was conducted in Kadapa district of Andhra Pradesh to identify various constraints perceived by dairy animal owners in dairy husbandry practices and data was collected from randomly selected 120 dairy animal owners through personal interview with the help of pre-tested structured schedule. The study revealed that constraints related to adoption feeding practices ranked first (72.77%) followed by constraints in adoption of housing practices (62.66%), milking practices (61.74%), health care practices (59.38%) and breeding practices (50.95%). High construction cost (85.00%), lack of knowledge of balancing ration (93.33%), repeat breeding in dairy animals (85.00%), inadequate knowledge of diseases and their control (95.00%) and non remunerative price for milk (87.50%) were the major constraints in adoption of improved animal husbandry practices by dairy farmers.